2016
DOI: 10.1111/ijfs.13178
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals content, antioxidant and hypoglycaemic activities of commercial nutmeg mace (Myristica fragrans L.) and pimento (Pimenta dioica (L.) Merr.)

Abstract: Summary Commercially dried powder of nutmeg mace (Myristica fragrans) and pimento (Pimenta dioica) spices was investigated for their high performance liquid chromatography phenolic profile and their antioxidant and hypoglycaemic properties by α‐amylase and α‐glucosidase inhibition tests. Generally, mace showed the most promising activity. An interesting protection of lipid peroxidation with an IC50 value of 7.7 μg mL−1 was found. A significant result was also obtained in ferric reducing ability power assay if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…The FRAP assay was utilized as previously described . The FRAP value represents the ratio between the slope of the linear plot for the reduction of the Fe 3+ ‐TPTZ reagent by different extracts compared to the slope of the plot for FeSO 4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FRAP assay was utilized as previously described . The FRAP value represents the ratio between the slope of the linear plot for the reduction of the Fe 3+ ‐TPTZ reagent by different extracts compared to the slope of the plot for FeSO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…The α‐glucosidase inhibition was measured as previously described . Both control and samples (at concentrations in the range of 0.01–1 mg mL −1 ) were added to the maltose solution and left to equilibrate at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Previous study has reported a lower activity of ME (75.7 µg/ml) when using mace commercial dried powder. 25 The ME was observed to have stronger inhibition than EAE (t = 7.96, p < 0.05). The strong relationship between α-glucosidase inhibitory activity (IC 50 ) and the total phenolic content was previously demonstrated in the literature 26 and gallic acidtype compounds may be responsible for the α-glucosidase inhibitory activity as reported previously.…”
Section: α-Glucosidase Inhibitory Activitymentioning
confidence: 90%
“…The research on ATR mainly focuses on its antioxidant activity. Some reports suggested that antioxidants can scavenge free radicals and reduce lipid peroxidation, protein peroxidation, and DNA damage of free radicals [ 10 , 11 ]. The studies on the antioxidants in food, plant materials, and TCMs recently attracted increasing attention [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%